2006
DOI: 10.1002/aic.10755
|View full text |Cite
|
Sign up to set email alerts
|

General friction theory viscosity model for the PC‐SAFT equation of state

Abstract: In this work, a general f-theory viscosity model based on the perturbed-chain statistical associating fluid theory (PC-SAFT) equation of state (EoS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 64 publications
0
87
0
Order By: Relevance
“…The dilute gas viscosity of the mixtures has been estimated by the mixing rule proposed in [38]. This mixing rule is a function of the composition and the dilute gas viscosity of the pure compounds.…”
Section: The Free-volume Theorymentioning
confidence: 99%
“…The dilute gas viscosity of the mixtures has been estimated by the mixing rule proposed in [38]. This mixing rule is a function of the composition and the dilute gas viscosity of the pure compounds.…”
Section: The Free-volume Theorymentioning
confidence: 99%
“…The most usual models to perform this task over broad pressure ranges are based on the freevolume concept, [33][34][35] the hard-sphere (Enskog) theory, [36][37][38][39] reaction rate theory, 40 or a friction model. 41,42 Other methods used to calculate viscosity based on molecular theory [43][44][45][46][47][48] (molecular simulation and QSPR methods) are not yet competitive for the studied systems. In this work, we have verified the prediction ability of the self-referencing method, the hard-sphere model, and the free-volume model.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work [96,97] has indicated f-theory gives accurate viscosity predictions at pressures up to 100 MPa when the friction coefficients  a ,  aa ,  r , and  rr are defined as exponential functions of reduced temperature. F-theory has been successfully used when the P a and P r inputs to Equation 32 is calculated using the PR, SRK, and PC-SAFT equations.…”
Section: Frictional Theory Of Viscosity (F-theory)mentioning
confidence: 99%
“…The two theories evaluated in this research that have shown great promise with regard to the accurate modeling of viscosity at both low pressures and HTHP conditions are the frictional theory (f-theory) [96,97] and the free volume theory (FV theory) of viscosity [98,99]. Detailed equations for both theories are provided in Appendix B.…”
Section: Frictional Theory (F-theory) and Free Volume Theory (Fv Theory)mentioning
confidence: 99%
See 1 more Smart Citation